TIGA DUNIA DALAM KAIN DODOT PENARI BEDOYO KETAWANG - - Mujiyanto (Imaji, 2012)
The motifs found in Dodot Batik are taken from natural elements such as birds, four-legged animals, snakes, flowers, butterflies, buildings, boats, corals, etc. Those motifs (Alasalasan motif) can be classified into three groups based on the natural areas to which they belong. Birds, butterflies, and the other things similar are regarded as the rulers of the upper nature, the place that belongs to Gods. Four-legged animals, flowers, etc. represents the middle nature, the place where human beings live. Meanwhile, snakes, boats, etc. represent the lower nature, in which those who have a bad life live. The three natural areas previously mentioned are inteded to remind human beings that they should remember God The Almighty, and they have to live their lives in surrender. If they live their lives in a wrong way, they would eventually find sorrow. Thus, in order to achieve a happy and peaceful life they have to remember God as well as to respect and appreciate each other. By doing all these, they will be united with God, which is exactly like what is presented in Alas-alasanmotifs in the clothes worn by Bedoyo KetawangDancers.